1998
DOI: 10.1016/s0896-6273(00)80455-9
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Analysis of Vertebrate Sensory Hair Cell Mechanosensation: the Zebrafish Circler Mutants

Abstract: The molecular basis of sensory hair cell mechanotransduction is largely unknown. In order to identify genes that are essential for mechanosensory hair cell function, we characterized a group of recently isolated zebrafish motility mutants. These mutants are defective in balance and swim in circles but have no obvious morphological defects. We examined the mutants using calcium imaging of acoustic-vibrational and tactile escape responses, high resolution microscopy of sensory neuroepithelia in live larvae, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
286
2

Year Published

1999
1999
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 284 publications
(300 citation statements)
references
References 45 publications
12
286
2
Order By: Relevance
“…After the microelectrode tip penetrated into the otic vesicle, the FM1-43X solution was pressure injected into the otic vesicle with a 10-ml syringe connected to the pressure port of the electrode holder. The injection was monitored under the Zeiss Axioskop microscope with the 40× water immersion objective lens and a Texas Red filter set in order to verify hair cell uptake of the dye, which is known to selectively and rapidly label sensory hair cells and then block their responses, presumably by entering mechanotransduction ion channels (Nishikawa and Sasaki 1996;Nicolson et al 1998;Gale et al 2001;Meyers et al 2003). FM1-43X was used as a control to rule out stimulus artifact as shown in Fig.…”
Section: Fluorescent Labeling With Fm1-43xmentioning
confidence: 99%
See 3 more Smart Citations
“…After the microelectrode tip penetrated into the otic vesicle, the FM1-43X solution was pressure injected into the otic vesicle with a 10-ml syringe connected to the pressure port of the electrode holder. The injection was monitored under the Zeiss Axioskop microscope with the 40× water immersion objective lens and a Texas Red filter set in order to verify hair cell uptake of the dye, which is known to selectively and rapidly label sensory hair cells and then block their responses, presumably by entering mechanotransduction ion channels (Nishikawa and Sasaki 1996;Nicolson et al 1998;Gale et al 2001;Meyers et al 2003). FM1-43X was used as a control to rule out stimulus artifact as shown in Fig.…”
Section: Fluorescent Labeling With Fm1-43xmentioning
confidence: 99%
“…Compared with mammals (see a review by Rübsamen and Lippe 1998), the zebrafish is a unique model for the study of early development of hearing and balance in vertebrates because the inner ear of zebrafish embryos is easily accessible for live imaging, physiological recording, and genetic manipulation (Waterman and Bell 1984;Haddon and Lewis 1996;Nicolson et al 1998;Bever and Fekete 2002;Whitfield 2002;Nicolson 2005;Zeddies and Fay 2005;Tanimoto et al 2011). Previous studies have reported on the development of auditory sensitivity in a few juvenile and adult teleosts using various physiological methods (Corwin 1983;Kenyon 1996;Higgs et al 2003;Sisneros and Bass 2005;Vasconcelos and Ladich 2008;Alderks and Sisneros 2011;Lechner et al 2012).…”
Section: Development Of Structure and Function Of The Inner Earmentioning
confidence: 99%
See 2 more Smart Citations
“…This simple behavior has been used to measure the spectral sensitivity and the visual sensitivity of this behavior in the adult goldfish visual system (Powers, 1978;Yager, 1968). In zebrafish, the DLR is only obvious in mutants with defects in their sense of balance (Nicolson et al, 1998). The response becomes much more pronounced when the fish is placed head down in a tightly fitting water-filled tube.…”
Section: Dorsal Light Response (Dlr)mentioning
confidence: 99%